Analisis Struktur Hidroksiapatit Berbasis Cangkang Telur Ayam dengan Variasi Suhu Kalsinasi - Ayunda Wulan Permatasari; Nailul Hasan; Nur Aini Fauziyah; Allif Rosyidy Hilmi (Universitas Andalas, 2026)
The purpose of this study is to understand how color changes occur during the calcination heating process at different temperatures in the formation of hydroxyapatite. The synthesis process began with the calcination of CaCO_3 to CaO at temperatures of 800°C, 900°C, and 1000°C for four hours, followed by the formation of hydroxyapatite thru the calcination process of eggshell samples at temperatures of 800°C and 1000°C for 3 hours. To determine the hydroxyapatite content in the sample, characterization was performed using XRD diffraction patterns to identify the phase. XRD analysis was conducted using match2 software. Morphological analysis of hydroxyapatite was performed using SEM characterization. The analysis results indicate that there are still impurities present at temperatures of 800-800°C. The higher the calcination temperature, the greater the purity of the resulting hydroxyapatite.